PENGARUH GEOMETRI DAN WINDOW TO WALL RATIO TERHADAP OVERALL THERMAL TRANSFER VALUE DAN KONSUMSI ENERGI PENDINGIN BANGUNAN - Mukhtar, Mufliha; Baharuddin Hamzah; Rosady Mulyadi (Nature : National Academic Journal of Architecture, 2023)
Generally, buildings consume around one-third of the world's total energy. Most of the energy in buildings in Indonesia is used by air conditioning systems. One effort to minimize energy waste in the building's air conditioning system is by lowering OTTV (Overall Thermal Transfer Value) to reduce external heat entering the building sheath. The study aims to analyze geometry and WWR (Window to Wall Ratio)’s influence on OTTV and building energy consumption through manual calculation and simulation processes on Autodesk Ecotect Analysis software. This research uses experimental quantitative methods by taking the Bosowa Tower located in Makassar as the research object to serve as a control variable in making alternative building models. The results showed that geometric and WWR variations in buildings were sufficient to affect OTTV values and cooling energy consumption. The smaller the ratio between the length and width of the base and the smaller the percentage of WWR in the building, the smaller the OTTV value and cooling energy consumption of the building. From this study, the most effective combination of geometry and WWR applied to buildings is the combination of 1:1 and WWR 15%.